1987
DOI: 10.2151/jmsj1965.65.2_259
|View full text |Cite
|
Sign up to set email alerts
|

Annual Deposition of Sr-90, Cs-137 and Pu-239, 240 from the 1961-1980 Nuclear Explosions: A Simple Model

Abstract: The annual deposition of 240, and Pu-238 were observed from 1959 to 1984 at the Meteorological Research Institute (MRI). In order to interpret the serial trends of the annual radioactive deposition at the MRI, a semi-empirical box model of atmospheric transport was developed. The model divides the atmosphere of the Northern Hemisphere into four compartments: the atmosphere above 21km, stratosphere below 2.1km, active mixing and exchange (AME) layer near the tropopause, and the troposphere. The transfer betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…1). The fallout 90 Sr in Japan is mostly derived from nuclear weapons tests from the 1950s to 1980s (Hirose et al 1987), and has experienced the aging for 15 to 55 y. Percentage of the fallout 90 Sr in the extractable fraction in the soil was similar to that of the freshly added Sr in the laboratory experiment within a year after the addition to the soil (Table 3; Fig.…”
Section: Discussionmentioning
confidence: 76%
“…1). The fallout 90 Sr in Japan is mostly derived from nuclear weapons tests from the 1950s to 1980s (Hirose et al 1987), and has experienced the aging for 15 to 55 y. Percentage of the fallout 90 Sr in the extractable fraction in the soil was similar to that of the freshly added Sr in the laboratory experiment within a year after the addition to the soil (Table 3; Fig.…”
Section: Discussionmentioning
confidence: 76%
“…[2] 137 Cs is an atomic fission product with a half life of 30 years, and most of the 137 Cs in the ocean was deposited the ocean surface in the early 1960s as part of the global fallout from large-scale atmospheric nuclear weapons' tests carried out during 1961-1962[Katsuragi and Aoyama, 1986Hirose et al, 1987;United Nations, 2000]. The 137 Cs deposition rate from global fallout varied by location, and the major deposition occurred in the western North Pacific (30 -45°N, 135 -155°E) [Aoyama et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of 90 Sr in Japan was mainly derived from nuclear weapons tests from the 1950s to 1980s (Hirose et al, 1987). Several researchers have previously reported that the fate of 137 Cs in the environment follows the transfer and distribution of stable Cs (Tsukada et al, 1998;Tsukada and Nakamura, 1999;Ru¨hm et al, 1999;Bunzl et al, 1999;Tsukada et al, 2002a, b;Tsukada and Hasegawa, 2002;Tsukada et al, 2003), therefore, the behavior of stable Sr in the environment should be regarded as a useful analogue in predicting the long-term fate of 90 Sr.…”
Section: Introductionmentioning
confidence: 99%